2017
DOI: 10.1093/qjmed/hcx005
|View full text |Cite
|
Sign up to set email alerts
|

AsthmaCOPD overlap syndrome showed more exacerbations however lower mortality than COPD

Abstract: Patients with ACOS were more likely to have better prognoses and lower mortality than those with COPD alone, though with greater exacerbation frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
10
2
1
Order By: Relevance
“…This compares with data available from China and the American continents, but contrasts with data available from other studies where no association was found between ACOS and exacerbation rates. [ 12 16 17 18 19 ] However, the criteria used to define ACOS may explain the difference recorded between our study and earlier studies. [ 20 ]…”
Section: Discussioncontrasting
confidence: 70%
“…This compares with data available from China and the American continents, but contrasts with data available from other studies where no association was found between ACOS and exacerbation rates. [ 12 16 17 18 19 ] However, the criteria used to define ACOS may explain the difference recorded between our study and earlier studies. [ 20 ]…”
Section: Discussioncontrasting
confidence: 70%
“…Older age has been identified as a risk factor associated with a higher prevalence of mortality in COPD patients. 19 , 20 Age (hazard ratio, 1.139; 95% confidence interval, 1.077–1.204; P <0.001) was independently associated with mortality from COPD. Many COPD patients simultaneously suffer from malignant tumor, cardiovascular disease, and other system diseases related to smoking, and these further affect the patients’ prognosis and survival time.…”
Section: Discussionmentioning
confidence: 99%
“… 4 8 The case of ACO is more controversial. While some authors report a higher incidence of exacerbation 9 , 10 and mortality in this phenotype, 11 , 12 others have not detected a higher incidence of exacerbations. 13 Compared with the other phenotypes of COPD, ACO has even been reported to have a “protective effect” against mortality.…”
Section: Introductionmentioning
confidence: 84%
“…Similar results were reported by Calle Rubio et al, 18 although this finding was not reported elsewhere. 10 , 14 …”
Section: Discussionmentioning
confidence: 99%